Selective Linguistic Approach in Islamic Legal Exegesis: A Multi-Dimensional Analysis of Ali al-Shabuni's Rawai' al-Bayan on Surah An-Nur - Putri, Neli; Syafruddin, Syafruddin; Huda, Yasrul; Suratman, Junizar (Potret Pemikiran, 2025)
Linguistic approaches constitute fundamental methodology in Qur'anic legal verse interpretation, yet systematic analysis of their application in contemporary exegesis remains limited. This study analyzes the linguistic approach employed in Muhammad Ali al-Shabuni's Rawai' al-Bayan Tafsir Ayat Ahkam, focusing on Surah An-Nur as a case study. Employing qualitative document analysis with Yin's five-stage analytical framework, this research examined nine legal themes across Surah An-Nur, mapping linguistic dimensions against classical lughawi exegesis standards. Al-Shabuni employs a selective multi-dimensional linguistic methodology integrating four primary dimensions: lexical analysis (al-tahlil al-lafzi), syntactic analysis (wujuh al-i'rab), morpho-phonological analysis (wujuh al-qira'at), and rhetorical-semantic analysis (latha'if al-tafsir). Distribution analysis reveals lexical and rhetorical approaches appear consistently across all themes, while morphological and syntactic analyses emerge selectively where grammatically consequential for legal interpretation. This functional selectivity demonstrates pedagogical innovation rather than methodological limitation, strategically deploying linguistic analysis to illuminate legally relevant textual features. Al-Shabuni's approach exemplifies sophisticated linguistic methodology, balancing scholarly rigor with pedagogical accessibility, and offers a replicable model for contemporary Islamic legal education that maintains fidelity to classical tradition while adapting to modern educational contexts